Molecular and morphological diversity, qualitative chemical profile and antioxidant activity of filamentous fungi of the digestive tract of Phylloicus sp. (Trichoptera: Calamoceratidae) - Romão,T. C. (2024)
Abstract This study aimed to identify by molecular analysis, morphology, chemistry and antioxidant extracts of filamentous fungi isolated from the digestive tract of Phylloicus sp, an aquatic insect that lives on leaf packages in tropical streams and participates together with fungi of the decomposition of plant substrates in aquatic habitats. Insect larvae of Phylloicus sp. were collected in streams in the state of Tocantins, Brazil. Fungi were isolated from the digestive tract of larvae after disinfection and dissection, then described and purified for identification purposes and testing for antioxidant activity. Molecular identity was performed of ITS1 and ITS4, TUB e TEF sequencing. Fungal extracts were produced in 70% ethanol solution and later lyophilized. For analysis of chemical groups of extracts, thin layer chromatography (TLC) was performed in two mobile phases and different developers. Morphology was performed by optical microscopy stained with Toluidine Blue and measurement performed using the ImageJ program. Antioxidant activity performed in TLC and by quantitative method for DPPH and hydrogen peroxide (H2O2) radicals. Four fungi were identified: Endomelanconiopsis endophytica, Myxospora musae, Neopestalotiopsis cubana and Fusarium pseudocircinatum. The TLC showed several spots with acetone/chloroform mobile phase and UV 254 nm developers and I2 vapor. Fungal extracts demonstrate antioxidant action to reduce the DPPH free radical and especially for H2O2 above 50%, E. endophytica 91.6%, M. musae 87.8%, N. cubana 89.5% and 92.3% for F. pseudocircinatum. This study demonstrated that the molecular technique by PCR was satisfactory for identifying fungi, and extracts with numerous chemical groups and potent reducing agents. Thus future work, should be carried out evaluating these four species for industrial use.